2012
DOI: 10.1007/s12160-011-9339-0
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Type D Personality and Prognosis in Patients with Cardiovascular Diseases: a Systematic Review and Meta-analysis

Abstract: More recent methodologically sound studies suggest that early type D studies had overestimated the prognostic relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
139
2
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(157 citation statements)
references
References 63 publications
5
139
2
8
Order By: Relevance
“…This adds to the growing literature on negative findings for Type D and prognosis (Coyne et al, 2011;Grande et al, 2012), and while a full discussion of potential reasons is beyond the scope of this literature, it may be due to cultural differences among countries.…”
Section: Tale 4 About Here Discussionmentioning
confidence: 84%
“…This adds to the growing literature on negative findings for Type D and prognosis (Coyne et al, 2011;Grande et al, 2012), and while a full discussion of potential reasons is beyond the scope of this literature, it may be due to cultural differences among countries.…”
Section: Tale 4 About Here Discussionmentioning
confidence: 84%
“…Grande and colleagues [35] performed such a meta-analysis of available studies and the resulting forest plot (Fig. 5 in [35]), offered a striking graphic representation of what was already known.…”
Section: Meta-analysis To the Rescue?mentioning
confidence: 99%
“…However, these studies have cast doubt on the association between Type D and mortality in cardiac patients. Furthermore, a recent meta-analysis [17] has suggested that the early studies on Type D may have overestimated the prognostic effect of Type D. Although the authors identified a significant association between Type D and mortality and non-fatal MI, they found that the identified odds ratios have decreased over time.…”
Section: Introductionmentioning
confidence: 98%